Russian Regions in the System of International Cooperation - GIBADULLIN, Marat Zufarovich; NURIEVA, Aigul Rustamovna; ILYASOVA, Asiya Mirgasimovna; GATINA, Farida Fargatovna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
This article is devoted to the research of international cooperation ties in Russian regions. Dynamics of foreign trade turnover in regions is investigated. The dynamics of foreign trade turnover of the Republic of Tatarstan is particularly researched. The authors proposed the method of analysis of international relations of the region on the basis of allocation of the core zone of international cooperation, whereas a core zone is a group of countries with which the researched region has had stable relations for a certain period of time. Special attention in the article is paid to the international relations and cooperation of the Republic of Tatarstan. The choice of this region of the Russian Federation is caused by the significant role of the Republic of Tatarstan in international relations of Russia and its economy. Confirmation of a hypothesis that participants of the international economic relations at the regional level form around themselves the zone of the international cooperation differing in heterogeneity is the result of scientific research. The offered technique can be used to carry out monitoring of international relations of the Russian regions.